Investigting caricatures of Haaretz and Al-Safir newspapers In the Battle of Israel and Gaza in the 2014 World Cup. [In Persian] - Saeedeh Sadat Moslem Aghili (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2019)
In today's society, due to development of public information tools, there is no possibility of ignoring important humanitarian events. If media does not try to provide people with an impartial approach to providing facts, motives and intellectual orientations, under the influence of their particular policies will be shaped in the society. Newspapers, as one of the most important traditional media, play a significant role in guiding public opinion. Caricature is one of the branches of visual arts that has a great use in delivering political and social messages. And cartoonists, who have a fairly quick response to events of the day, devote some pages of newspapers to political and social caricatures, and therefore, present their ideas according to the ends of media. The war between Palestine and Israel is a matter of great importance over the last few decades in all media across the world. And various press, according to their political stances, analyze certain parts of the war, some of which are in the direction of the Palestinian resistance, and some of them act in the opposite direction. In this study, two popular paper, Haaretz (Israel) and al-Asfir (Lebanon), which have a significant impact and have two different approaches, have been analyzed. And by comparing the caricatures in these two newspaper during the Israeli invasion to Gaza in 2014 World Cup, the success rate of these media has been investigated in conveying the proposed concept, according to its policies.